2022
DOI: 10.1186/s12958-022-00970-x
|View full text |Cite
|
Sign up to set email alerts
|

Diverse actions of sirtuin-1 on ovulatory genes and cell death pathways in human granulosa cells

Abstract: Background Human granulosa-lutein cells (hGLCs) amply express sirtuin-1 (SIRT1), a NAD + -dependent deacetylase that is associated with various cellular functions. SIRT1 was shown to elevate cAMP on its own and additively with human chorionic gonadotropin (hCG), it is therefore interesting to examine if SIRT1 affects other essential hGLC functions. Methods Primary hGLCs, obtained from the follicular aspirates of women undergoing IVF and SV40-transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 85 publications
3
16
0
1
Order By: Relevance
“…Controversial results were reported on SIRT1's impact on GC viability from various species, which will be described below [51][52][53][55][56][57]. In a recent study aimed to reveal the effect of SIRT1 on hGLC viability, SRT2104 was incubated with intact primary hGLCs and SVOG cells or with SIRT1-silenced cells [51,53]. It was found that SRT2104 dose-and time-dependently decreased viable cell numbers.…”
Section: Sirt1 Activation and Gc Healthmentioning
confidence: 99%
See 4 more Smart Citations
“…Controversial results were reported on SIRT1's impact on GC viability from various species, which will be described below [51][52][53][55][56][57]. In a recent study aimed to reveal the effect of SIRT1 on hGLC viability, SRT2104 was incubated with intact primary hGLCs and SVOG cells or with SIRT1-silenced cells [51,53]. It was found that SRT2104 dose-and time-dependently decreased viable cell numbers.…”
Section: Sirt1 Activation and Gc Healthmentioning
confidence: 99%
“…Studies with SVOG cells have produced results comparable to those obtained in primary cells, demonstrating that they indeed serve as a reliable model for hGLCs [9, 51, 53, 85, 86]. For example, as will be detailed below, both cell types responded similarly to different SIRT1 activators in terms of SIRT1 induction, various GCs' gene expression as well as cell viability [21, 51, 53].…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations